Adding Rhizobium for Soybean Planting to Create Nitrogen from Bacteria in the Soil and Productive Comparison - LERDPANAN , Bounma; SITTHIVOHAN3 , Insavai; LOCHAMYEU, Chanthavong (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This study was set a purpose to research on soybean planting for creating nitrogen from bacteria in the soil (Rhizobium) and productive comparison. The experimental design was located at farmer’s village, Ban Xainado, Kham district, Xiengkhuang Province. Assessment was conducted with productivity of farmer’s soybean cultivation, the implementation of this study was started from 5th May to 5th October, 2017, and it spent 5 months. This study was applied by Randomized Completely Block Design (RCBD) with 4 replications and 3 treatments. T1= Soy bean planting without Rhizobium (Control). T2 = mixed Rhizobium with seed before planting (Thailand). T3 = mixed Rhizobium with seed before planting (England). The total area of design was 23m x 16m = 368 m2. It was used program Sirichai statistic 6.07 for analysis. The result of this study was found the best treatment that created nitrogen’s gland from rhizobium bacteria in soybean was rhizobium from England such as mixed Rhizobium with seed before planting (England) was provided 18. 800 glands, at the same time, mixed Rhizobium with seed before planting (Thailand) was offered only 15.100 glands and Soy bean planting without Rhizobium (Control) was presented lowest. The productivity of soybean found that all the treatments adding England’s rhizobium bacteria was received highest yield as 938 kg/ha, therefore treatments that added Thailand’s rhizobium bacteria was represented 809 kg/ha. However, the result showed that adding organism especially any species of rhizobium bacteria can transferred nitrogen to the soil and received higher yield of soybean.